function |
the derived equivalent formula |

Secant (secant) |
SEC (x) = 1/cos (x) |

Cosecant (more cut) |
Cosec (x) = 1/sin (x) |

Cotangent (cotangent) |
Cotan (x) = 1/tan (x) |

Inverse Sine (anyway chord) |
Arcsin (x) = Atn (X/SQR (-X * x + 1)) |

Inverse cosine (anti-cosine) |
Arccos (x) = Atn (-X/SQR (-X * x + 1)) + 2 * ATN (1) |

Inverse secant (anyway cut) |
ARCSEC (x) = Atn (X/SQR (x * X-1)) + SGN ((x)-1) * (2 * ATN (1)) |

Inverse cosecant (anti-surplus cut) |
Arccosec (x) = Atn (X/SQR (x * X-1)) + (SGN (x)-1) * (2 * ATN (1)) |

Inverse cotangent (anti-cotangent) |
Arccotan (x) = Atn (x) + 2 * ATN (1) |

Hyperbolic Sine (hyperbolic sine) |
HSin (x) = (exp (x)-exp (-X))/2 |

Hyperbolic cosine (hyperbolic cosine) |
Hcos (x) = (exp (x) + EXP (-X))/2 |

Hyperbolic Tangent (hyperbolic tangent) |
Htan (x) = (exp (x)-exp (-X))/(EXP (X) + exp (-X)) |

Hyperbolic secant (hyperbolic secant) |
Hsec (x) = 2/(exp (x) + exp (-X) |

Hyperbolic cosecant (double curved Cut) |
Hcosec (x) = 2/(exp (x)-exp (-X) |

Hyperbolic cotangent (hyperbolic cotangent) |
Hcotan (x) = (exp (x) + exp (-X))/(exp (x)-exp (-X)) |

Inverse hyperbolic Sine (inverse hyperbolic sine) |
Harcsin (x) = Log (x + SQR (x * x + 1)) |

Inverse hyperbolic cosine (inverse hyperbolic cosine) |
Harccos (x) = Log (x + SQR (x * X-1)) |

Inverse hyperbolic Tangent (inverse hyperbolic tangent) |
Harctan (x) = Log ((1 + x)/(1-x))/2 |

Inverse hyperbolic secant (anti-hyperbolic secant) |
Harcsec (x) = Log ((SQR * x + 1) + 1)/x) |

Inverse hyperbolic cosecant (anti-hyperbolic cut) |
Harccosec (x) = Log ((SGN (x) * SQR (x * x + 1) + 1)/x) |

Inverse hyperbolic cotangent (anti-hyperbolic cotangent) |
Harccotan (x) = Log ((x + 1)/(X-1))/2 |

Logarithm with N as the base |
Logn (x) = log (x)/log (N) |